2021
DOI: 10.16899/jcm.758144
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Dönemde Annelerin Bebek Beslenmesi Tutumlarını Etkileyen Faktörler

Abstract: To investigate the factors affecting mothers' infant feeding attitudes in the postpartum period.Material and Method: Crosssectional descriptive research was carried out in a public hospital child outpatient clinic. The sample of the study consisted of 173 mothers whose babies were followed up in the pediatric outpatient clinic between April 2018 and April 2019. The data were obtained through the questionnaire form and the Infant Nutrition Attitude Scale.Results: A statistically significant difference was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…the correct use of theories and models in health education (13)(14)(15). In the studies carried out, the breastfeeding problems experienced by the mother and the breastfeeding attitude affect the way she feeds her baby and the duration of breastfeeding (16,17). According to the results of this metaanalysis, it was found that theory-based interventions increased the knowledge about breastfeeding in mothers and showed only breastfeeding attitude.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 97%
“…the correct use of theories and models in health education (13)(14)(15). In the studies carried out, the breastfeeding problems experienced by the mother and the breastfeeding attitude affect the way she feeds her baby and the duration of breastfeeding (16,17). According to the results of this metaanalysis, it was found that theory-based interventions increased the knowledge about breastfeeding in mothers and showed only breastfeeding attitude.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 97%
“…Bulgularımız, bu konuda yapılmış benzer çalışmaların bulguları ile benzerdir. 9,15,19,27,30 Çalışmamızda annelerin öz-yeterlilik düzeyi arttıkça anne sütü verme eğilimlerinin arttığı saptanmıştır. Literatürde annelerin kendilerini emzirme konusunda yeterli ve başarılı hissettiklerinde ve emzirme konusunda desteklenip öz-yeterlilikleri yükseltildiğinde emzirme başarılarının arttığı bulunmuştur.…”
Section: Bulgularunclassified